Education on the Utilization of Broccoli (Brassica oleracea L. Var italica) as a Preventive Measure for Myopia at SMA Negeri 2 Banjarmasin - Awilda, Pertiwi; Chairul; Nurwahida; Nurrahmah, Sheila; Rahima, Siti; Kartini (Journal of Social and Community Service, 2022)
Myopia is a growing public health issue worldwide, including in Indonesia. Preventive measures include educating the public about the importance of nutrition for eye health. This community service program was conducted at SMA Negeri 2 Banjarmasin in April 2022, aiming to educate students about the benefits of broccoli (Brassica oleracea L. var italica) as an essential nutritional source for preventing myopia. Broccoli is rich in vitamin C, lutein, zeaxanthin, and beta-carotene, which are known to benefit eye health. The program utilized methods such as pre-tests, interactive educational sessions, broccoli preparation demonstrations, and post-tests to evaluate knowledge improvement. Results showed a significant increase in students' understanding of broccoli's benefits for eye health, with average pre-test scores of 56.7 rising to 85.4 in the post-test.